Justiz zwischen Diktatur und Demokratie. Wiederaufbau und Ahndung von NS-Verbrechen in Westdeutschland 1945-1949 - Raim, Edith 1965- (Quellen und Darstellungen zur Zeitgeschichte, 2013)
The firmly established view is that the German justice system utterly failed in its responsibilities after 1945. Edith Raim does not turn this interpretation on its head, but she relativizes it in many respects. Her starting point is the nuanced history of West German justice after 1945, including an examination of the passionate discussions between the Allies and Germany about Nazi "crimes against humanity